Correlations between the expression of molecules in the TGF-β signaling pathway and clinical factors in adamantinomatous craniopharyngiomas - Jin, Lu; Cai, Kefan; Wu, WenTao; Xiao, Youchao; Qiao, Ning; Liu, Fangzheng; Ru, Siming; Cao, Lei; Zhu, Haibo; Bai, Jiwei; Liu, Chunhui; Li, Chuzhong; et al. (Frontiers in Endocrinology, 2023)
Objective: To investigate the clinical and pathological factors associated with the preoperative hypothalamus invasion and postoperative outcomes of adamantinomatous Craniopharyngiomas (ACPs) after the expanded endonasal approach (EEA) resection.Methods: ninety-three specimens of ACPs, including 71 primary and 22 recurrent tumors, were investigated for the expression of TGFB1, SMAD2, SMAD3, and β -catenin by immunohistochemistry staining. The clinical information of relevant patients, including extent of resection, hypothalamus invasion, endocrinopathy, complications, and prognosis, was reviewed. The relationships between expression of these immunopathological markers and clinical factors were analyzed.Results: Endocrinological dysfunctions were more common in the recurrent patients and primary patients with hypothalamus invasion in the comparisons. For recurrent patients, the rate of gross-total resection (GTR) was significantly lower than primary patients (63.6% vs. 90.1%, P=0.007). According to radiological and intraoperative findings, invasive ACPs (IACPs) included 48 (67.6%) cases in primary tumors. The expression of TGFB1 and β-catenin were significantly higher in the recurrent tumors (P=0.021 and P=0.018, respectively) and IACPs ( P=0.008 and P=0.004, respectively). The expression level of TGFB1 was associated with the hypothalamus involvement (Puget grade, P=0.05; Vile grade, P=0.002), postoperative endocrinopathy (P=0.01), pituitary stalk preservation (P=0.008) in primary patients. In addition, the extent of resection, treatment history, hypothalamic invasion, and level of TGFB1 expression had significant influences on the tumor recurrence/progression after surgery, separately.Conclusion: Our study demonstrated the potential role of TGFB1 in regulation of hypothalamus invasion in ACPs and prediction of prognosis after EEA surgery. TGFB signaling pathway may represent a crucial mechanism in the aggressive behavior and progression of ACPs.